Both Whistleblowers and the Scientists They Accuse Are Vulnerable and Deserve Protection. (18th August 2017) - Bouter, Lex M.; Hendrix, Sven
ABSTRACT: Whistleblowers play an important role diagnosing research misconduct, but often experience severe negative consequences. That is also true for incorrectly accused scientists. Both categories are vulnerable and deserve protection. Whistleblowers must proceed carefully and cautiously. Anonymous whistleblowing should be discouraged but cannot be ignored when the allegations are specific, serious, and plausible. When accused of a breach of research integrity it is important to be as transparent as possible. Sometimes accusations are false in the sense that the accuser knows or should know that the allegations are untrue. A mala fide whistleblower typically does not act carefully and we postulate a typology that may help in detecting them. Striking the right balance between whistleblower protection and timely unmasking false and identifying incorrect accusations is a tough dilemma leaders of research institutions have to face.